1983
DOI: 10.1055/s-2008-1037077
|View full text |Cite
|
Sign up to set email alerts
|

Tokolyse mit Hexoprenalin und Salbutamol im klinischen Vergleich*

Abstract: 140 patients with a threatening premature birth at the greater than or equal to 24-less than 37 week of gestation were in this study randomly treated with hexoprenalin or salbutamol. In 77% in the hexoprenalin and in 74% in the salbutamol group the weight of the newborn was greater than or equal to 2500 g. In 66% in both study groups the birth occurred after the completed 37 weeks of gestation. During infusion of hexoprenalin tachycardia in mothers occurred statistically highly significantly less than during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Five to six hours after beginning oral treatment the serum salbutamol concentration is still high enough when the next tablet is taken. Up to now it has been reconimended that the first oral tablet is taken 30 min before discontinuation of intravenous treatment, to ensure sufficiently high plasma levels of fi-mimetics (Gummerus 1983). The present results show that the first tablet can be taken 4-6 h after stopping infusion.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Five to six hours after beginning oral treatment the serum salbutamol concentration is still high enough when the next tablet is taken. Up to now it has been reconimended that the first oral tablet is taken 30 min before discontinuation of intravenous treatment, to ensure sufficiently high plasma levels of fi-mimetics (Gummerus 1983). The present results show that the first tablet can be taken 4-6 h after stopping infusion.…”
Section: Discussionmentioning
confidence: 65%
“…Thus salbutamol, for example. has more cardiac and circulatory side-effects reflecting (3,-receptor action than hexoprenaline (Gummerus 1983). High doses used in intravenous treatment tend to have both (3,and fi2-rcccptor effccts.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the characteristics of the trials and comparison of the quality of tocolytic studies retrieved are reported elsewhere 16. Twenty five trials contained a placebo arm (26%),27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 60 included beta mimetics (63%),27 28 29 31 34 35 36 37 39 43 46 48 50 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 29 included magnesium sulfate (31%),29 30 33 38 47…”
Section: Resultsmentioning
confidence: 99%